The War in Ukraine and the Potential of Facebook’s Social Connectedness Index to Anticipate Human Displacement - International Organization for Migration (United Nations, 2023)
Authored by Umberto Minora, Martina Belmonte, Claudio Bosco, Drew Johnston, Eugenia Giraudy, Stefano M. Iacus and Francesco Sermi, this Migration Research Series paper highlights the importance of anticipating conflict-induced migration flows through innovative data from social media to support national and local authorities in terms of reception and integration. The paper explores the potential of Facebook’s Social Connectedness Index for predicting migration flows in the context of the war in Ukraine, building on previous research findings that the presence of a diaspora network is one of the major migration drivers. Results suggest that the index, along with other readily available covariates, is a strong predictor of the Ukrainian diaspora at regional scale.